2005
DOI: 10.1215/s1152851704000584
|View full text |Cite
|
Sign up to set email alerts
|

Well-differentiated neurocytoma: What is the best available treatment?

Abstract: Most neurocytomas are well differentiated, being associated with better long-term survival than the more aggressive atypical lesions. Atypical neurocytomas are characterized by an MIB-1 labeling index >3% or atypical histologic features. This analysis focuses on well differentiated neurocytomas in order to define the optimal treatment. A case with a follow-up of 132 months is presented. The patient developed two recurrences two and four years after first surgery, each showing an increasing proliferation activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
1
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 42 publications
2
71
1
4
Order By: Relevance
“…Rades et al (12) have documented that postoperative radiotherapy improved the local control and survival rates of patients with incomplete resection. The optimal dose of radiotherapy appears to be 54-60 Gy (3).…”
Section: Discussionmentioning
confidence: 99%
“…Rades et al (12) have documented that postoperative radiotherapy improved the local control and survival rates of patients with incomplete resection. The optimal dose of radiotherapy appears to be 54-60 Gy (3).…”
Section: Discussionmentioning
confidence: 99%
“…Central neurocytomas usually arise from the neuronal cells of the septum pellucidum, fornix, or subependymal plate of the lateral or third ventricle, so these tumors are surrounded by cerebrospinal fluid and occur as a small tumor attached to normal structures. 7,8,10,16,26,27,31) Therefore, radiosurgery has a lower risk of radiation injury than conventional radiotherapy because of the small target volume, relatively low marginal dose for tumor growth control, and steep fall-off into the peripheral normal tissue. The present series included no complication caused by radiation-induced peripheral edema or radiation necrosis, and previous studies identified only one case of side effects (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…3,4,6,7,11,12,14,15,17,21,24,27,29,30,32) Central neurocytoma tends to be radiosensitive, so postoperative conventional radiotherapy and radiosurgery have been used to treat residual tumors after incomplete surgical resection or recurrence. 15,20,[23][24][25][26]31,32,34) Gamma knife radiosurgery (GKS) is effective against postoperative residual tumors or local recurrences of central neurocytomas. [1][2][3]6,9,13,14,25,27,28,35,37) However, central neurocytoma is rare and often resected completely, with conservative treatment for the relatively small residual or recurrent tumors.…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that central neurocytomas are genetically distinct from oligodendrogliomas. Although the expression profiles of cerebellar liponeurocytomas appear to have a closer relationship to those of central neurocytomas, the lack of TP53 mutations in central neurocytomas suggests the involvement of different genetic pathways (60,66,67).…”
Section: Genetic Susceptibilitymentioning
confidence: 99%
“…The glial components seen in the complex forms of DNTs have a highly variable form due to many causes : 1-they may form typical nodules with diffuse pattern; 2-they may mimic usual categories of gliomas and may illustrate unusual features; 3-they usually resemble low-grade gliomas, but may demonstrate nuclear atypia, some mitotic activity, or microvascular-like proliferation and ischemic necrosis; 4-they display a microvascular network. Within the glial components, typically calcified vessels are frequent that may behave as vascular malformations and be responsible for bleeding (65,66,86,99,101,103,104,105). "Non-specific" histological variants of DNTs, identified according to clinical presentation as well as their cortical location, neuroimaging features, and steadiness on long-term preoperative imaging follow-up, have been described (77).…”
Section: Complex and Non Specific Formsmentioning
confidence: 99%